Increasing customer service efficiency through artificial intelligence chatbot (REGE Revista de Gestão, 2022)
Purpose – This study investigated the contribution of artificial intelligence (AI) to the efficiency of customerservice. This study contributes to services technological innovation in process management, a field not yetsettled in the literature.Design/methodology/approach – AI is a multidisciplinary field of research that has stood out for thetechnological dynamism provided to organizational products and processes. The study was carried out at anAnalytical Intelligence Unit (AIU) of a Brazilian commercial bank that applies AI integrated with IBM’s Watsonsystem. The study used data content analysis, structured and supported by Atlas.ti software.Findings – The notorious AI cognitive maturity evolution allowed 181 million interactions and 7.6 millionattendances in 2020, improving services efficiency, with gains in agility, availability, accessibility, resoluteness,predictability and transshipment capacity. The chatbot service reduced the queues of call centers andrelationship centers, allowing the human attendant to perform more complex attendances.Research limitations/implications – The main limitations of this study relate to the research cutout and itsborders, such as the choice of participants and their areas of activity, and the choice of the unit of analysis.Practical implications – The results indicated that attendance through the virtual assistant increased bymore than a 1,000% from 2019 to 2020, demonstrating the bank was technologically ready to face the Covid-19pandemic effects.Originality/value – In line with the evolutionary theory of innovation, the authors concluded thattechnological scaling in AI allows exponential gains in customer service efficiency and business processmanagement. They also conclude that the strategy for creating AIUs is successful, once it allows centralizing,structuring and coordinating AI projects in R&D cooperation, cognitive computing and analytics.